Osteologia e miologia cranianas de Psophiidae (Aves: gruiformes) - Marceliano, Maria Luiza Videira (Museu Paraense Emilio Goeldi, 2016)
Evolucionary relationships among the families within the Gruiformes are nOl yel well established. In an allempt to establish relationships among them, the cranial osteology of ali Psophiidae was studied and also data from the jaw musculature were obtained from P. viridis. These data were compared wilh representatives of Aramidae, Rallidae, Heliornithidae and Eurypygidae. The results on cranial osteology showed no significam differences among the species of Psophiide. An outstanding characteristic of the species ofPsophia is the presence of three bony trabecula, two from the shull (squamosal process) and one from the mandible (pseudotemporal tubercle) . However, when data of cranial osteology from Psophiidae and jaw musculature of P. viridis were compared with species from the other families of the Gruifof7!2es, many differences in structure were observed. The inconclusive situation in the literature concerning the Gruiformes' relationships continues. It is suggested that a systematic study ofthesefamilies be conducted to establish the true relationships among the groups.